Changes in cardiac structure over 25 years are associated with lower midlife cognition: The CARDIA study: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Rouch, Laure; Hoang, Tina D; Xia, Feng; Sidney, Stephen; Lima, Joao; Yaffe, Kristine
Abstract: Background: Cardiovascular risk factors are associated with worse cognition, yet less is known about the impact of cardiac structure and function and their adverse effects on the brain possibly from decreased perfusion. The few studies included older patients with cardiovascular disease and relied on single echocardiographic assessment. Method: We included 2256 subjects from the CARDIA (Coronary Artery Risk Development in Young Adults) study (60% women, 44% black). Echocardiograms were repeated at Years 5, 25, 30 (mean age 30, 50, 55 years, respectively) to assess cardiac structure: left ventricular mass (LVMi), left atrial volume (LAVi) and systolic function: left ventricular ejection fraction (LVEF). Diastolic function was assessed at Year 25 as the ratio of early peak mitral velocity (E)/early peak mitral annular velocity (e'). Five cognitive domains were assessed at Year 30: verbal memory [Rey Auditory Verbal Learning Test (RAVLT)], category and letter fluency, processing speed [Digit Symbol Substitution Test (DSST)], executive function [Stroop] and global cognition [Montreal Cognitive Assessment MoCA]. We investigated the association of (1) 25‐year change and (2) Year 25 cardiac structure and function on midlife cognition using linear regressions. Result: Over 25 years, LVMi and LAVi increased with mean change (SD) of 5.7 g/m² (21.7) and 9.6 mL/m² (7.4) while LVEF decreased by mean (SD) change of 1.5% (9.0). After adjustment for demographics and education, abnormal cardiac structure assessed by greater 25‐year increase (≥ 1‐SD) in LVMi was associated with lower cognition on most tests: RAVLT (6.2 vs. 6.8, p<0.001), DSST (59.7 vs. 61.7, p=0.02), Stroop (29.0 vs. 27.2, p=0.01) and MoCA (19.1 vs 19.7, p=0.001). Similarly, greater 25‐year increase in LAVi was associated with lower MoCA (19.8 vs. 20.3, p=0.04). Further adjustment for hypertension, diabetes and smoking reported similar findings. 25‐year decrease in LVEF was not associated with cognition. In addition, higher Year 25 LVMi, LAVi and E/e' ratio were significantly associated with worse cognition on most cognitive tests. Conclusion: Midlife cardiac structure and its change from early to middle adulthood are associated with lower midlife cognition. Moreover, midlife diastolic but not systolic function is linked to cognition. Our results provide novel information linking cardiac structure and function to cognition.